2012
DOI: 10.2134/jeq2011.0157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Addition on Greenhouse Gas Emissions and Microbial Responses in a Short-Term Laboratory Experiment

Abstract: Biochar application to soil has drawn much attention as a strategy to sequester atmospheric carbon in soil ecosystems. The applicability of this strategy as a climate change mitigation option is limited by our understanding of the mechanisms responsible for the observed changes in greenhouse gas emissions from soils, microbial responses, and soil fertility changes. We conducted an 8-wk laboratory incubation using soils from PASTURE (silt loam) and RICE PADDY (silt loam) sites with and without two types of bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 50 publications
5
51
0
7
Order By: Relevance
“…Concurrently, the CO 2 emissions from agricultural soil also increased with biochar addition during the first N deposition event (Fig. 1c), which is consistent with the results of Yoo and Kang (2012). These findings can be partly explained by the following facts: right after the incorporation of biochar into soils, volatile biochar compounds (aliphatic compounds) may act as decomposable organic C sources in soil and thus provide a readily available substrate for denitrifying microorganisms (Blagodatskaya and Kuzyakov 2008;Ameloot et al 2013); due to the priming effect (soil microbial community has been stimulated due to the addition of various organic amendments), biochar incorporation with a high C/N ratio may stimulate soil microorganisms to decompose SOM (Kuzyakov et al 2000;Bünemann et al 2006;Smith et al 2010;Nelissen et al 2012).…”
Section: Discussion N 2 O Co 2 and Nh 3 Emissions Affected By N Deposupporting
confidence: 87%
“…Concurrently, the CO 2 emissions from agricultural soil also increased with biochar addition during the first N deposition event (Fig. 1c), which is consistent with the results of Yoo and Kang (2012). These findings can be partly explained by the following facts: right after the incorporation of biochar into soils, volatile biochar compounds (aliphatic compounds) may act as decomposable organic C sources in soil and thus provide a readily available substrate for denitrifying microorganisms (Blagodatskaya and Kuzyakov 2008;Ameloot et al 2013); due to the priming effect (soil microbial community has been stimulated due to the addition of various organic amendments), biochar incorporation with a high C/N ratio may stimulate soil microorganisms to decompose SOM (Kuzyakov et al 2000;Bünemann et al 2006;Smith et al 2010;Nelissen et al 2012).…”
Section: Discussion N 2 O Co 2 and Nh 3 Emissions Affected By N Deposupporting
confidence: 87%
“…Anderson et al [75] concluded that adding biochar to the soil potentially increased microbial N cycling, especially the abundance of those organisms that may decrease N 2 O fluxes and NH 4 + concentrations. Conversely, Yoo and Kang [61] suggested the higher N 2 O fluxes observed in the presence of swine manure-derived biochar in paddy soils was partially a consequence of higher denitrifier abundance.…”
Section: Biochar and Soil Biotamentioning
confidence: 97%
“…To date, several studies have shown that the addition of biochar to soils can mitigate N 2 O emissions in situ from soybean and grass ecosystems [48], following ruminant urine deposition [49], in wheat plots [50] and during laboratory or greenhouse incubations under various conditions [8,9,47,[51][52][53][54][55][56][57][58][59][60][61] while other studies have found no differences or even increases in cumulative N 2 O emissions after biochar addition [61][62][63].…”
Section: Mitigation Of Nitrous Oxide Emissions Using Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar ash content, pyrolysis conditions, and C/N ratios seem to be key factors influencing N2O emissions, while a direct correlation has been found between biochar application rate and N2O emission mitigation (Liu et al 2012;Cayuela et al 2014). The ability of environmentally sound biochar to sequester carbon in soils depends on the characteristics of the receiving soil, as well as the structure and composition of the biochar (Lehmann et al 2011;Yoo and Kang 2012). Biochars, in comparison to composts, tend to sequester C, yet a combination of both might be desirable for sustaining long-term fertility of soils (Bolan et al 2012).…”
Section: Introductionmentioning
confidence: 99%